Muḥammad al-Ṣūfī, the Prophet Muḥammad, and Ibn al-Fāriḍ: Creative Trends in Arabic Religious Poetry in the 9th/15th Century - Homerin, Th. Emil (Journal of Sufi studies, 2020)
Abstract Muḥammad Ibn al-Shihābī al-Ṣūfī composed mystical poems in praise of the prophet Muḥammad, basing much of his verse on the poems of Ibn al-Fāriḍ. While he was not the first to imitate Ibn al-Fāriḍ, Ibn al-Shihābī may have been the first Arabic poet to use consistently a Persian style signature verse ( takhalluṣ ). This article offers a critical Arabic edition, English translation, and analysis of several of his poems, with a particular focus on his signature verses, which add insights into Ibn al-Shihābī’s life, religious beliefs, and vocation as a Sufi eulogist of the Prophet.